The Role of Social Interaction in Shaping Social Psychological Dynamics of Community Life - Ummi, Khaisya Sabina Nazarul; Majid, Abdul; Alkautsar, Ridha (Journal Social Humanity Perspective, 2025)
The paper analyses the role that social interaction plays in forming the social psychological effects of the manner in which societies choose to live binding the impacts of how people relate to the establishment of unity, trust and strength in societies. This paper has used the qualitative approach to conduct research using the in-depth interviews and observation techniques as tools of gathering lived experiences and daily activities that reflect on intricate correlation between patterns in interactions and the well-being of the community. The findings indicate that social interaction concerns not only development of the communication, but a unified perception of identity, a sense of support and adaptability, which determine a high level of importance in a multiethnic and diverse community. The results show that social psychological processes such as solidarity, empathy, collective efficacy, emerge automatically at the end of a long interaction process to create or develop mechanisms to assist in resolving conflicts, in addition to the solution of communal challenges. The problems were also pointed out including the cultural tension, generation gap and lack of shared participation around which the cohesion may be threatened but not dealt with effectively. The findings are significantly applicable in the field of management, as they reiterate the necessity of looking at the connection and the psychology of the community governance and organizational strategizing. With the prominence of social interaction in the frontline, the study will help in facilitating the development of more participatory, adaptive and people-centered approaches to management of community and institutions. The lesson learned by the study is, that sustainable community management cannot be limited merely to structural, economic, interventions, but also must focus on developing solid social psychological processes as an important vehicle to sustained resilience and development.